Assessment of Fibroblast Growth Factor- 23 and Klotho Protein in Children with Steroid-Sensitive Nephrotic Syndrome and Steroid-Resistance Nephrotic Syndrome - Hatem Alwan, Ahmed; Al-Shammaa, Nawal M.J. (Iraqi Journal of Pharmaceutical Sciences, 2025)
Idiopathic nephrotic syndrome is a common disease that affects children’s kidneys and occurs due to a specific defect in the glomeruli, which leads to the leakage of protein into urine in large quantities. Fibroblast growth factor-23 (FGF-23), produced by bone, is essential for controlling the metabolism of 1,25-dihydroxy vitamin D and phosphate, but it also requires the Klotho co-receptor to perform its function. Therefore, the purpose of this study was to evaluate whether FGF-23 can be used as a biomarker to determine the likelihood of recurrent relapse as well as to differentiate between steroid-sensitive nephrotic syndrome (SSNS) and steroid-resistant nephrotic syndrome (SRNS) treated with glucocorticosteroids. In this cross-sectional study, 85 patients with idiopathic nephrotic syndrome were divided into four groups: Out of 50 children included in this study with (SSNS) were grouped in the first group (20) in relapse and the second (30) in remission, in addition to 35 child had (SRNS) were divided as: the third group of (20) in the relapse phase and the fourth group of (15) in the remission phase, while the control group included 40 healthy children. The fibroblast growth factor (FGF-23) levels and its co-receptor Klotho were measured in these patients using an ELISA kit. Our results revealed that serum levels of FGF-23 were significantly elevated in steroid-sensitive NS with a mean of (51.73 ng/L) in relapse and (16.49 ng/L) in remission, while for the steroid-resistant groups (67.25 ng/L) in relapse and (24.66 ng/L) in remission, compared with the control group with a mean of 7.73 ng/L (P < 0.0001). At the same time, Klotho concentrations were decreased for all patient groups compared with the control group. Hence, FGF-23 serum level is a potential biomarker to identify patients with frequent relapses at a cutoff value (16.055 ng/L). While its ability to distinguish between SSNS and SRNS patients was lower at a cut-off value of (20.00 ng/L).